Pour la fête de notre séraphique mère sainte Thérèse: A Teresian Celebration in Verse, and a Concise View of French Carmelite Poetry. - HANNA, DANIEL (Scripta)
This article commemorating the 500th anniversary of the birth of Teresa of Avila has two purposes: one, the presentation and analysis of a newly discovered poem composed in honor or Teresa of Avila in the French Carmelite convent of Saint-Denis (Paris) and two, a brief overview of recent scholarly work on French Carmelite poetry. It is proposed in the article that the poems of Teresa of Avila, not always considered important in their own right, should be re-considered and re-contextualized as foundational texts in a long tradition of Carmelite poetry that is both international and multilingual.